Avaliação de programas de desenvolvimento comunitário: o caso do FUNDEC - Bezerra, Walter Faco (1996)
The present study aims to create an evaluation model of Fundo de Desenvolvimento Comunitário (FUNDEC), program instituted by Banco do Brasil S.A. in 1981 and administered, today, by Banco do Brasil Foundation. The study can be classified as an evaluation research, as it intend to construct an instrument of assessing program effectiveness. Fundamentally, the research was conducted in order to formulate performance measures that could confirm or not the community development where the FUNDEC goes, specially in the field of democratization. The most important attributes considered by the study were those related to the quality of individual life of the population aided by the Program, emphasizing the aspect of citizen participation. Evaluation's dimensions, indicators and variables were determined by using participant observation, which characterize the study also as qualitative methodology. The constructed model was appiied in small city located in northeast of Rio de Janeiro's state, Brazil.